2019
DOI: 10.1016/j.heliyon.2019.e01697
|View full text |Cite
|
Sign up to set email alerts
|

A novel non-ionic surfactant extract derived from Chromolaena odarata as shale inhibitor in water based drilling mud

Abstract: High performance clay swelling inhibitors play a vital role in improving inhibition characteristics of shales. The linkages between the inhibition's characteristics of the non-ionic surfactant extract from bio-based inhibitors are yet to be fully explored in the literature. This paper reports the use of a crude extract containing saponins from Chromolaena odorata (CO) leaf, which act as surfactants for inhibiting shale hydration. Determination of the inhibitive property of nonionic surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…They consist of a hydrophilic head and a hydrophobic tail. Mostly, nonionic and cationic surfactants are used as inhibitors (Aggrey et al, 2019). These surfactants are adsorbed on the surface of swelling clays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They consist of a hydrophilic head and a hydrophobic tail. Mostly, nonionic and cationic surfactants are used as inhibitors (Aggrey et al, 2019). These surfactants are adsorbed on the surface of swelling clays.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive study of different surfactants in preventing shale swelling has been done with little focus on the potential use of gemini cationic surfactants (Aggrey et al, 2019;Ghasemi et al, 2019). Gemini cationic surfactants are a comparatively new class that contains two lipophilic tails and two lipophobic headgroups chemically bonded by the spacer (Menger and Keiper, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…During drilling shale, it is crucial to add high-performance clay swelling inhibitors to the drilling fluid as a preventive approach since that will function as a pivotal role in enhancing inhibition characteristics of shales. Aggrey et al (2019) showed the feasibility of utilizing chromolaena odorata (CO) leaf. Their results showed that CO can serve out as surfactants for inhibiting shale hydration.…”
Section: Applications Of Waste Materials and Usesmentioning
confidence: 99%
“…In addition, it had the potential to work through plugging and viscosity acting effects in the shale system. Aggrey et al (2019) ended up with some conclusions associated with CO leaf performance, including but not limiting to the similarity between CO crude and industrial potassium chloride (KCL) in all inhibition features, establishing the capability to maximize the shale formation strength as temperature increases, providing a good stability bentonite particles in CO aqueous solution. Finally, CO crude extract is readily extractable at minimal price and easily obtainable as a substitute for commercial KCL.…”
Section: Applications Of Waste Materials and Usesmentioning
confidence: 99%
“…Several studies have been conducted to investigate the potential of surfactants as a shale swelling inhibitor [ 48 , 49 ]. It was noticed that surfactants showed promising potential as a swelling inhibitor by modifying the surface properties of the clay.…”
Section: Introductionmentioning
confidence: 99%